The Fourth Industrial Revolution and the New Path of Law - Simonyan, Taron (Bulletin of Yerevan University C: Jurisprudence, 2023)
The contemporary accelerating changes in technology lead to drastic transformations in economy, social and political structures, as well as legal practice and the very essence of law. The present research is a try to bring to the light the evolution of industrial revolutions and realize the transformations and developments of law and legal practice throughout the First, Second, Third and Fourth Industrial Revolutions. Taking into account the consequences of the previous industrial revolutions and the ongoing nature of the Fourth Industrial Revolution, the research defines some general developments / paths in the law, especially the transformations in legal practice (Practical Perspective); transformations in teaching law (Educational Perspective) and transformation in the essence and perception of law itself (Theoretical Perspective). Based on the research two possible social structures, with economic, political and legal order, have been proposed: negative and positive.